A Simple Digital Thermometer; Instruments and Experimental Techniques; Vol. 63, iss. 3 - Filatov A. V. Aleksandr Vladimirovich; Kobzev V. M. Vyacheslav Mikhaylovich; Filatov N. A. Nikolay Alexandrovich; Serdyukov K. A. Konstantin Alekseevich; Novikova A. A. Anastasiya Alekseevna (2020, 2020)
Title screen